Spring and Summer Cover Crop Effects on Dryland Wheat and Grain Sorghum Yields in Western Kansas - L. M. Simon; A. K. Obour; J. D. Holman; S. K. Johnson; K. L. Roozeboom (Kansas Agricultural Experiment Station Research Reports, 2022)
Incorporating cover crops (CC) to replace fallow in traditional dryland cropping systems in the semi-arid conditions of western Kansas has the potential to enhance soil health, suppress weeds, and increase precipitation use efficiency. The returns from haying or grazing can help cover costs of CC establishment and any reduction in yield from the subsequent grain crop. Two studies were initiated in 2015 and 2016 near Brownell, KS, to investigate dual-purpose spring and summer CC management effects on subsequent grain yields in a three-year no-till (NT) dryland winter wheat-grain sorghum-fallow cropping system. Cover crops were planted in early spring between grain sorghum and winter wheat or in mid-summer soon after wheat harvest. Cover crops were grazed with yearling heifers, hayed at a six-inch stubble height, or left standing (no forage removal). All CC treatments were compared to NT fallow with no CC. Results showed spring CCs reduced wheat yields between 25 and 31% compared to fallow (59 bu/a) in two of three years, with no difference in the other year. Wheat yields were not different among CC management strategies. Summer CCs reduced grain sorghum yields at rates up to 39% compared to fallow (67 bu/a) in one of three years only when CCs were grazed or left standing but not when CCs were hayed. Sorghum yields were not different in the other two years. Yields of wheat or grain sorghum grown more than one year following CCs in the crop rotation were unaffected by CC treatments. These results showed CCs reduced subsequent crop yields compared to fallow. However, grazed or hayed CCs had no negative effects on dryland wheat and grain sorghum yields compared to standing CCs. Allowing grazing or haying of CCs on land enrolled in Natural Resources Conservation Service cost-share programs could increase producer adoption of CCs in semi-arid western Kansas to enhance regional soil health and increase dryland cropping system profitability.
Keywords: cover crops; dryland; wheat; grain sorghum